Quasi-continuous parallel online scattered light, fluorescence and dissolved oxygen tension measurement combined with monitoring of the oxygen transfer rate in each well of a shaken microtiter plate. Issue 1 (December 2016) - Ladner, Tobias; Held, Markus; Flitsch, David; Beckers, Mario; Büchs, Jochen
Abstract Background Microtiter plates (MTP) are often applied as culture vessels in high-throughput screening programs. If online measuring techniques are available, MTPs can also be applied in the first steps of process development. For such small-scale bioreactors dipping probes are usually too large; therefore, optical measurements are often used. For example, the BioLector technology allows for the online monitoring of scattered light and fluorescence in each well of a continuously orbitally shaken MTP. Although this system provides valuable data, these measurements are mainly of a semi-quantitative nature. Therefore, signal calibration is required to obtain absolute values. With the µRAMOS technology it became possible for the first time to quantify the oxygen transfer rate (OTR) separately in each well of an MTP. In this work, a device is presented that combines both techniques, to provide a hitherto unparalleled high amount of information from each single well. Results Because both systems (BioLector and µRAMOS) are based on optical measurements, the measurements need to be synchronized to avoid interferences with the optical signals. The new experimental setup was applied for online monitoring in cultures ofEscherichia coli andHansenula polymorpha . It has been demonstrated that the well-to-well reproducibility is very high, and that the monitored signals provide reliable and valuable information about the process. With varying filling volumes, different maximum oxygen transfer capacities (OTRmax ) were adjusted in oxygen-limited cultures. The different degrees of stress during the culture due to oxygen limitation affected microbial growth and also impacted reproducibility from culture to culture. Furthermore, it was demonstrated that this new device significantly simplifies the experimental efforts: instead of parallel cultures in a shake flask and MTP, just one single experiment in MTP needs to be conducted to measure the OTR, dissolved oxygen tension (DOT), scattered light and fluorescence. Conclusions The new device is a very suitable system for the online monitoring of cultures in continuously orbitally shaken MTPs. Due to the high number of parameters that can simultaneously be measured with this small-scale device, deeper insight into the investigated microbial system can be achieved. Furthermore, the experimental efforts to obtain OTR, DOT, scattered light and fluorescence signals during a culture are decreased. Ultimately, this new technology and the resulting high amount of collected data will eliminate the currently existing separation between screening and process development.Graphical abstract Picture of the combined μRAMOS and BioLector setup which allows for measurements of the oxygen transfer rate (OTR), dissolved oxygen tension (DOT), scattered light and fluorescence in each single well of an orbitally shaken microtiter plate.